Systematic Literature Review : E-LKPD Berbantuan Liveworksheets Untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik - mira utami; Rani Refianti; Maria Luthfiana (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
This research was prepared using the Systematic Literature Review (SLR) method with stages 1) Research Question; 2) Selection Criteria; 3) Search Strategy; 4) Select Studies; 5) The Quality Of Studies; and 6) Synthesis Results. Article searches were obtained from Google Scholar, Sinta, Scopus and Garuda using the keywords E-LKPD, Liveworksheets, and understanding mathematical concepts. The articles studied consisted of 10 Sinta and Scopus indexed articles published in 2020-2024. The purpose of reviewing this article is to emphasize the importance of developing teaching materials that support active learning in increasing students' understanding of mathematical concepts. The results of research using the Systematic Literature Review method show that the development of Liveworksheets-assisted E-LKPD is declared to have met the feasibility test in terms of material, media, and trial results in both small and large groups. So this E-LKPD is declared valid, practical and effective for use in learning. Thus, E-LKPD assisted by Liveworksheets can make a positive contribution in increasing the effectiveness of mathematics learning, especially in increasing students' understanding of concepts